Emodin in cardiovascular disease: The role and therapeutic potential - Guo, Yuanyuan; Zhang, Rongzhen; Li, Wenlan (Frontiers in Pharmacology, 2022)
Emodin is a natural anthraquinone derivative extracted from Chinese herbs such as Rheum palmatum L, Polygonum cuspidatum, and Polygonum multiflorum, is now also one of the commonly used clinical drugs and is listed in the Chinese Pharmacopoeia. Emodin has a wide range of pharmacological properties, including anticancer, anti-inflammatory, antioxidant, and antibacterial effects. Many in vivo and in vitro experiments have also demonstrated that emodin has potent anti-cardiovascular activity. Emodin exerts different mechanisms of action in different types of cardiovascular diseases, including involvement in pathological processes such as inflammatory response, apoptosis, cardiac hypertrophy, myocardial fibrosis, oxidative damage, and smooth muscle cell proliferation. Therefore, emodin can be used as a therapeutic drug against cardiovascular diseases and has a broad application prospect. This paper summarizes the main pharmacological effects and related mechanisms of emodin in cardiovascular diseases in recent years, and also discusses the limitations of emodin in terms of extraction preparation, toxicity, and bioavailability-related pharmacokinetics in clinical applications.